(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2014)
The investigations conducted by the University of Milan from 2003 on the site of Gortyna were concentrated in the south area of the so-called Praetorian Quarter, bringing to light a thermal building, the “Terme Milano”, which were built on the ruins of the Hellenistic stadium in the second half of the fourth century AD. The complex shows different fases of use that extend up to the second half of the seventh century AD, when the building fell into disrepair. Subsequently, the area was exploited for the recovery of building materials and partially invaded by modest houses.